AN INTERNATIONAL COMPARISON OF GRADE 6 STUDENTS' UNDERSTANDING OF THE EQUAL SIGN - (:unkn) unknown (AMMONS SCIENTIFIC, LTD, 2010)
This study extends the scope of international comparisons examining students' conceptions of the equal sign. Specifically, Korean (n=193) and Turkish (n=334) Grade 6 students were examined to assess whether their conceptions and responses were similar to prior findings published for Chinese and U.S. students and to hypothesize relationships about problem types and conceptual understanding of the equal sign. About 59.6% of the Korean participants correctly answered all items providing conceptually accurate solutions, as compared to 28.4% of the Turkish sample. Comparison with previous studies in China and the USA indicated that the Chinese sample outperformed those from other nations, followed by Korea, Turkey, and the USA. In large-scale international studies such as Trends in International Mathematics and Science (TIMSS) and the Programme for International Student Assessment (PISA), students from China and Korea have been among the high achievers.